Best-Practice - Mobile Testing Viewing mobile usability studies with the example of an eyetracking study in the retail sector - Karsten Zischner (Proceedings of the International Conference on Applied Innovations in IT, 2013)
Today, usability testing in the development of software and systems is essential. A stationary usability lab offers many different possibilities in the evaluation of usability, but it reaches its limits in terms of flexibility and the experimental conditions. Mobile usability studies consider consciously outside influences, and these studies require a specially adapted approach to preparation, implementation and evaluation. Using the example of a mobile eye tracking study the difficulties and the opportunities of mobile testing are considered.